Management of Post-Operative Endophthalmitis with Intravitreal Vancomycin and Amikacin - Salim, Mahmoud A.; Abukheir, Babiker Haga (Gezira Journal of Health Sciences, 2017)
Aims : To assess the outcome of management of post-operative endophthalmitis with intravitreal injections of Vancomycin and Amikacin; both by measuring the visual acuity and assessing the corneal transparency. The study also aimed at identifying the causative organism, by culture and sensitivity and Gimsa staining of the vitreal tap. Materials and methods: This study was conducted in Makkah eye complex, Khartoum – Sudan, over a period from April 2003 till December 2004. Patients reported at out patient department(OPD) with signs and symptoms of endophthalmitis within six weeks after cataract surgery, they were examined initially for the visual acuity; then diffuse illumination and bio-microscopy examination was performed for grading clarity of cornea, and for checking presence of hypopyon or sufficient clouding of the anterior chamber, also intraocular inflammation was measured by the assessment of flare, cells, and inflammation membrane. Indirect ophthalmoscopy was performed to examine the red fundal glow and the status of the vitreous and retina. Inside the operating room vitreous and aqueous tap were done for the culture and sensitivity. Then the patients were treated with intravitreal and subconjuctival injection of Amikacin and Vancomycin. Results: In a total of (25) patients, pain and blurring of vision were found to be the most common symptoms, Insufficient corneal clarity 23 (92%) of patients, hypopyon was found at different levels in all patients, Red reflex was absent in 21 (84%) of patients. All the patients were found to have either vitritis, choroiditis or both in A and B scan. Post treatment findings of the 19 (76%) patients who attended the final six-month follow-up were as follow: The pain was relieved in all patients. The visual acuity had improved to a maximum of 6/18 one (5%) patient, 2 (10.5%) patients went into phthisis bulbi. The clarity of cornea was observed in 17 (89.5%) patients. Hypopyon disappeared from 17 (89.5%) of patients after injection. Fundal glow reappeared in 12 (63%) of patients. The results of remaining 6 (24%) patients who attended less than three-month follow-up period were as follow: Pain was relieved in (5) 83% of patients. The visual acuity reached a maximum of 3/60 in (1) 16.7% of patients, (1) 16.7% of the patients went into phthisis bulbi. The clarity of cornea was observed in (5) 83% of patients. (3)50% of patients were having no hypopyon after injection, fundal glow remains absent. Cultures were negative in (15) 60% of cases. (10) 40% showed confirmed growth of different organisms. Staphylococcus aureus (1) 4%, S. viridance (1) 4%, S. epidermidis (2) 8%, S. pyogenes (3) 12% and S. albus (3) 12%.